COMPARISON OF NEUTRON REFLECTION AND SURFACE-TENSION MEASUREMENTS OF THE SURFACE EXCESS OF TETRADECYLTRIMETHYLAMMONIUM BROMIDE LAYERS AT THE AIR-WATER-INTERFACE - Simister, E; Thomas, R; Penfold, J; Aveyard, R; Binks, B; Cooper, P; Fletcher, P; Lu, J; Sokolowski, A (1992)
Neutron reflection and surface tension (ring and plate methods) have been used to study the adsorption of four deuterated isotopic species of tetradecyltrimethylammonium bromide (C14TAB) at the air/water interface at 298 K. The critical micelle concentration (cmc) was found to be (3.7 ± 0.1) × 10-3 M for three of the four isotopic species, in good agreement with earlier determinations. The fourth species showed a slight surface tension minimum but was otherwise similar. The close similarity of the surface tension curves indicated that the surface properties of C14TAB are independent of deuteration, a result of importance for the interpretation of neutron reflectivity. Neutron reflection has been used to measure the surface concentrations of the fully deuterated and chain-deuterated isotopes of C14TAB from 3 × 10-4 to 4.5 × 10-3 M. The area per molecule at the cmc (A) was found to be 46 ± 2 Å2 and continues to decrease above the cmc. The γ-ln c plots gave a limiting area per molecule at the cmc, which depended on both the method used to determine γ and the method of analysis of the data. The simplest approach using a Pt-Ir ring and a straight line plot gave a value of 60 Å2, in agreement with some earlier determinations, but, using a plate and a polynomial fit to the data, the value was found to be in close agreement with the neutron measurement, i.e., 45 ± 2 Å2. The implications of the difficulty in determining A from surface tension measurements are discussed in detail. © 1992 American Chemical Society.